Main law cultures in the world - Karsznicki, Krzysztof (Studia Iuridica Toruniensia, 2015)
A result of a meeting between representatives of different cultures can be a conflict, which will be a surprise for both sides. A reason of such conflict will not be a conflict of interests. The reason will be different hierarchy of values and interpretation of the opponent’s behavior. This is very important in a case of different law cultures. There are the following law cultures in the world: Judaism, Christianity, Islam, Hinduism, Confucianism and animism. Of course, some representatives of these cultures live or lead business in Poland more often, other ones more rarely. Anyway the problem is very important. The culture difference can be reason of committing an offence, but also can negative influence criminal investigation, for example when a man is interrogated by a woman.